2014
DOI: 10.1016/j.cmet.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Initial Steps in RNA Processing and Ribosome Assembly Occur at Mitochondrial DNA Nucleoids

Abstract: Mammalian mitochondrial DNA (mtDNA) resides in compact nucleoids, where it is replicated and transcribed into long primary transcripts processed to generate rRNAs, tRNAs, and mRNAs encoding 13 proteins. This situation differs from bacteria and eukaryotic nucleoli, which have dedicated rRNA transcription units. The assembly of rRNAs into mitoribosomes has received little study. We show that mitochondrial RNA processing enzymes involved in tRNA excision, ribonuclease P (RNase P) and ELAC2, as well as a subset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
90
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 57 publications
(81 reference statements)
14
90
2
3
Order By: Relevance
“…It is tempting to speculate that Dss1 supports a similar directed turnover of damaged mRNAs. Interestingly, we observed that Suv3 is a component of the nucleoid-MIOREX assembly and not part of the peripheral complexes, in line with previous data showing a preferential nucleoid interaction (Bogenhagen et al, 2014). Because Suv3 and Dss1 have to interact for efficient degradation (Malecki et al, 2007), this observation suggests a functional cycle of translation: MIOREX complexes adjacent to the nucleoid are charged with newly transcribed pre-mRNAs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is tempting to speculate that Dss1 supports a similar directed turnover of damaged mRNAs. Interestingly, we observed that Suv3 is a component of the nucleoid-MIOREX assembly and not part of the peripheral complexes, in line with previous data showing a preferential nucleoid interaction (Bogenhagen et al, 2014). Because Suv3 and Dss1 have to interact for efficient degradation (Malecki et al, 2007), this observation suggests a functional cycle of translation: MIOREX complexes adjacent to the nucleoid are charged with newly transcribed pre-mRNAs.…”
Section: Discussionsupporting
confidence: 83%
“…These RNA granules also contain RNA-binding proteins, methyltransferases, and ribosomal proteins, therefore likely representing the nucleoid-MIOREX complexes identified here. In addition to a role of the RNA granules in organizing the early steps of gene expression, it was demonstrated that also ribosome assembly occurs in proximity to the nucleoid (Bogenhagen et al, 2014;He et al, 2012). Because of technical difficulties in working with mitochondrial ribosomes, it was not known how the fully assembled ribosome is related to these structures.…”
Section: Discussionmentioning
confidence: 97%
“…Human NOA1 (hNOA1), also known as MTG3 or C4orf14, is associated with the nucleoid and is necessary for SSU assembly (61)(62)(63). We have also identified ERAL1 in nucleoids (29,64). ERAL1 is a GTPase that functions as an RNA chaperone, binding to the TFB1M-mediated dimethylation region of 12 S rRNA (65,66), potentially folding the RNA into the proper conformation needed for SSU assembly.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to finding methyltransferases localized near nucleoids, we have recently shown that newly synthesized MRPs are localized in the nucleoid complex to encounter newly synthesized rRNA using pulse-chase stable isotope labeling by/with amino acids in cell culture labeling (29). It is also known that GTPases are important for mitoribosome assembly, just as they are for bacteria (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation